Successful summer reading programs for all ages a practical guide for librarians - Fitzgerald, Katie (Lanham, Maryland. Rowman & Littlefield, 2018)
The summer reading program is the focal point of a children’s librarian’s year, requiring countless hours of preparation and nearly year-round promotion. Summer reading programs for teens and adults are also offered in many communities, adding to that workload and bringing together librarians from different departments to accomplish the required tasks. In a single volume, Successful Summer Reading Programs for All Ages: A Practical Guide for Librarians provides the tools necessary to put together successful summer reading programs for each of these different age groups. --Provided by publisher.
Includes bibliographical references and index.
Keywords: Summer reading programs -- United States -- Handbooks, manuals, etc; Libraries -- Activity programs -- Handbooks, manuals, etc; Books and reading -- United States -- Handbooks, manuals, etc; Reading programs, Summer; Summer vacation reading programs; Vacation reading programs, Summer; Libraries -- Activity programs